Pengendalian Erosi dan Limpasan Permukaan Menggunakan Teknik Mulsa Vertikal pada Budidaya Jeruk Manis di Lahan Miring - Abdul Rauf (Jurnal Agrista, 2008)
Controlling of Soil Erosion and Run-off by Vertical Mulch Technology on the Citrus Cultivation at Hill SlopeABSTRACT. The effects of vertical mulch applications on erosion control and run-off, also soil properties and fertility on citrus cultivations at hill slope had been done in July to November, 2007 in buffer zone of Gunung Leuser National Park, Rumah Galuh Village, Sei Bingei Sub-district, Langkat district, with 560 meters altitude, and 22,5% land slope. Two vertical mulch application are: vertical mulch having the same aim with contour line, and ring vertical mulch. The conservations methods were studied are pile having the same aim with contour line, pile ring, ring of mulch in gunny-sack. Two control experiments are: horizontal mulch application, and without mulch application. These result are: vertical mulch applications could control erosion and run-off and affected physical and chemical soil properties better than horizontal mulch application. The best of conservation methods application where controlling erosion and and run-off are contour pile and mulch in gunny-sack, and affected on soil physical and biological properties are ring vertical mulch, but for affecting soil chemical properties are mulch in gunny-sack.